CLINICAL MANIFESTATIONS IN POSITIVE COVID 19 PATIENTS WITH AND WITHOUT VACCINATED - Aurora, Wahyu Indah Dewi; Nuriyah, Nuriyah; Sulistiawan, Andika; Darmawan, Armaidi; Maria, Ima; Kusdiyah, Erny (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
ABSTRACT Introduction: Since the emergence of Emerging Diseases, namely the discovery of a new virus in 2019 which was named Covid-19, the World Health Organization (WHO) has established a Pandemic status throughout the world. To anticipate the large number of fatalities, it is necessary to have a vaccine to reduce morbidity and mortality. The purpose of this study was to find out the differences in clinical manifestations that appeared in patients with positive Covid-19 before and after receiving vaccination. Method: The design of this study was Cross Sectional conducted at the Puskesmas/Clinic in Jambi City from April to October 2022. The number of samples used was 721 samples using the simple random sampling technique, the medical records of patients positive for Covid 19 were taken randomly at the Puskesmas/Clinic/ Hospitals that meet the inclusion criteria will be included as samples. Results: From the results of the study, the most samples were aged 21-30 years (35.2%). Based on gender, there were 330 respondents (45%). From the results of the study, it was found that the percentage of respondents who had fever (62.41%), coughing (50.5%), body weakness (32.4%), itching in the throat (21.63%), runny nose/runny nose (44.8%), dizziness/headache (25.65%). Pain in muscles and joints (25.4%), nausea (13.6%), vomiting (5%), diarrhea (5.3%), fever (26.5%), chest pain (5.8%) ), loss of sense of smell (20.24%), loss of sense of taste (13.86%), itching of the skin (2.35%), and other symptoms such as disorders of the eyes, ears, etc. as much as 8.8% . Conclusion: The clinical manifestations of patients who are positive for Covid 19 are milder in respondents who have been vaccinated compared to those who have not been vaccinated. Keywords: Clinal Manifestation Covid-19, Vaccine